(untitled) (Ameghiniana, 2017)
We restudy a fragment of femur unhearted from Cueva del Milodón (Late Pleistocene; southern Chile) and originally referred to “a large extinct rodent” or Megamys. We conclude that this material can not be differentiated from a camelid and probably belongs to a form similar to Lama guanicoe. Therefore, we remove Megamys from Late Pleistocene faunal assemblages from southern Chile and the and the necessity to explain the survival of giant dinomyids at high latitudes.